2018
DOI: 10.1177/0004867418768432
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and educational outcomes of maltreated and non-maltreated youth: A birth cohort study

Abstract: Child maltreatment, including both abuse and neglect, is associated with adverse cognitive, educational and employment outcomes in young adulthood. This adds further impetus to efforts to prevent child maltreatment and assist young people who have experienced it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 46 publications
1
20
0
Order By: Relevance
“…Initial child protection reports are predicated on suspected abuse, neglect, or harm, with substantiated forms of severe maltreatment sometimes resulting in placement in out of home care (OOHC). Globally, child maltreatment has been linked to an array of maladaptive outcomes in later life, including physical and mental health problems (Cicchetti & Doyle, 2016; Gilbert et al, 2009), low academic attainment (Fantuzzo et al, 2011; McGuire & Jackson, 2018), unemployment (Mills et al, 2018), and crime (Widom, 2017). Identifying vulnerable children as early as possible is crucial for the implementation of opportune interventions that improve children’s long-term outcomes (Olds, 2008; Sanders et al, 2014), given that maltreatment at earlier stages in development is associated with significantly poorer outcomes in later life (Kaplow & Widom, 2007; Mersky et al, 2012).…”
mentioning
confidence: 99%
“…Initial child protection reports are predicated on suspected abuse, neglect, or harm, with substantiated forms of severe maltreatment sometimes resulting in placement in out of home care (OOHC). Globally, child maltreatment has been linked to an array of maladaptive outcomes in later life, including physical and mental health problems (Cicchetti & Doyle, 2016; Gilbert et al, 2009), low academic attainment (Fantuzzo et al, 2011; McGuire & Jackson, 2018), unemployment (Mills et al, 2018), and crime (Widom, 2017). Identifying vulnerable children as early as possible is crucial for the implementation of opportune interventions that improve children’s long-term outcomes (Olds, 2008; Sanders et al, 2014), given that maltreatment at earlier stages in development is associated with significantly poorer outcomes in later life (Kaplow & Widom, 2007; Mersky et al, 2012).…”
mentioning
confidence: 99%
“…Advanced analytical methods included generalised linear models (GLM) [108], multinomial logistic regression using Vermunt's three step Latent Class Analysis approach and Growth Mixture Modelling [92], and survival analysis using Kaplan-Meier, Cox (proportional hazards) regression and Nelson-Aalen Estimation methods [55,99]. A few studies used a combination of methods, where in most cases logistic regression was included as one of the main methods [45,47,55,82]. Only one study reported descriptive statistics as their main method of analysis [109].…”
Section: Methodsmentioning
confidence: 99%
“…In the majority of studies, baseline data consisted of prenatal or postnatal data as reported by the mothers, while outcome data were obtained during follow-up waves. Six major longitudinal studies were reported from the publications, the main one being the Mater-University Study of pregnancy (MUSP) which was conducted in Queensland, Australia from 1981-2004 [58,[80][81][82]. While these studies had multiple follow-up waves, the authors mostly reported on the baseline wave and one follow up wave.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…23 A state-based birth cohort study has explored a range of health and developmental outcomes with limited analysis of maltreatment through agency records of substantiated reports, which relied on 512 children with substantiated maltreatment from a cohort of 7223 mother-infant pairs. [24][25][26][27][28] Another statebased birth cohort study assessed young people's childhood victimisation and psychosocial outcomes, 29 and a national longitudinal study has considered parenting behaviours more generally. 30 However, no study has aimed to use a nationally representative sample to comprehensively measure the prevalence and nature of all five forms of child maltreatment, and their associations with mental and physical health and health risk behaviours.…”
Section: Introductionmentioning
confidence: 99%